2016
DOI: 10.1515/jolace-2016-0003
|View full text |Cite
|
Sign up to set email alerts
|

The use of English language outside the classroom

Abstract: This article presents a study which aimed to explore in what ways Armenian EFL students use their English language knowledge outside the classroom. The study involved 38 EFL learners of different English proficiency levels, ages, and genders. Data were collected using surveys and in-depth interviews. Findings indicate that most of the Armenian EFL learners use English out of the class very often, especially with social media, listening to songs, watching movies and clips, as well as travelling and searching on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 6 publications
2
13
0
Order By: Relevance
“…These findings are similar to those of Sargsyan and Kurghinyan (2016), but in contrast to Orhon's (2018) study, Henry (2014) found gender-related outof-class English learning differences among school students in Sweden. Male participants spent more time on such interactive activities as computer games and at the same time improved their vocabulary and oral skills outside the classroom (Henry, 2014, p. 4), while more female than male participants thought they learned English in class more than outside the classroom (Henry, 2014, p. 15).…”
Section: Literature Review On Out-of-class English Language Learningsupporting
confidence: 72%
See 2 more Smart Citations
“…These findings are similar to those of Sargsyan and Kurghinyan (2016), but in contrast to Orhon's (2018) study, Henry (2014) found gender-related outof-class English learning differences among school students in Sweden. Male participants spent more time on such interactive activities as computer games and at the same time improved their vocabulary and oral skills outside the classroom (Henry, 2014, p. 4), while more female than male participants thought they learned English in class more than outside the classroom (Henry, 2014, p. 15).…”
Section: Literature Review On Out-of-class English Language Learningsupporting
confidence: 72%
“…A variety of research in Asia has confirmed it (Sargsyan & Kurghinyan, 2016;Tantarangsee et al, 2017;Lee et al, 2011), but in Finland, which is culturally closer to Lithuania, the students improve both receptive and productive skills almost equally frequently outside of their classroom (Moncrief, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some other researches (Chusanachoti, 2009, Grau, 2009, Maros & Saad, 2016, Sargsyan & Kurghinyan, 2016, Sundqvist, 2009, the scholars obtained more or less similar results, that is, students of various ages in their free time engage in technology-based receptive language activities like watching movies or videos, surfing on the Internet, social media, etc. which are considered as a kind of entertaining activities.…”
Section: Discussionmentioning
confidence: 89%
“…Grau (2009) discovered the activities outside the classroom in which German students engage in their free time and the obtained data shows that out-of-class English is not incorporated in the language classroom. Furthermore, Sargsyan and Kurghinyan (2016) state that Armenian EFL students employ English outside the classroom mostly via social media, listening to music, watching films, traveling, and surfing on the Internet, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%